2021
DOI: 10.3389/fsufs.2021.624203
|View full text |Cite
|
Sign up to set email alerts
|

Plant Microbiota Beyond Farming Practices: A Review

Abstract: Plants have always grown and evolved surrounded by numerous microorganisms that inhabit their environment, later termed microbiota. To enhance food production, humankind has relied on various farming practices such as irrigation, tilling, fertilization, and pest and disease management. Over the past few years, studies have highlighted the impacts of such practices, not only in terms of plant health or yields but also on the microbial communities associated with plants, which have been investigated through micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 178 publications
0
12
0
Order By: Relevance
“…The effect of the aboveground cover on belowground microorganisms has been reported under different agroecological conditions, ranging from pot trials to natural ecosystems. Cropping affects soil microorganisms through many factors including cultivation regimes, plant cover and age, root exudates, and soil types (Berg and Smalla, 2009 ; Reinhold-Hurek et al, 2015 ; Compant et al, 2019 ; Delitte et al, 2021 ). Experimental data from assays carried out under controlled conditions (with faba bean and wheat plants) for example, showed an effect of the plant species on the soil fungal communities profiles, with differences related to the sample origin (bulk soil or rhizosphere).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the aboveground cover on belowground microorganisms has been reported under different agroecological conditions, ranging from pot trials to natural ecosystems. Cropping affects soil microorganisms through many factors including cultivation regimes, plant cover and age, root exudates, and soil types (Berg and Smalla, 2009 ; Reinhold-Hurek et al, 2015 ; Compant et al, 2019 ; Delitte et al, 2021 ). Experimental data from assays carried out under controlled conditions (with faba bean and wheat plants) for example, showed an effect of the plant species on the soil fungal communities profiles, with differences related to the sample origin (bulk soil or rhizosphere).…”
Section: Discussionmentioning
confidence: 99%
“…The soil microbiome and its interactions with plants play a key role in plant development, reproduction, and overall health (e.g., plant growth-promoting rhizobacteria; Berendsen et al, 2012;Wei et al, 2019;Figure 2c). In recent years many studies have shown that global warming, climate change, and the increased levels of pollutants in different soils around the world can cause a significant decline in the complexity and composition of the soil microbiome, raising the alarming possibility that this decline would also affect agricultural productivity (Delitte et al, 2021;Rillig et al, 2019b;Sergaki et al, 2018). In addition to the root microbiome, found primarily at the plant rhizosphere, plants also harbor microbiomes on their above-ground surfaces (i.e., their phyllosphere), or internally between their cells (i.e., their endosphere), and all three microbiomes are thought potentially to promote plant growth and enhance resistance to different stresses (Figure 2c).…”
Section: Soil Microbiome and Stress Combinationmentioning
confidence: 99%
“…Soil microorganisms occupy only a minuscule portion (0.5%) of the total volume of soil [54] could be a predictor for evaluating soil quality [50,55]. They act in SOM decomposition, nutrient cycling, soil aggregation, and soil health [56][57][58].…”
Section: Microbial Populationmentioning
confidence: 99%